¿Drugs as part of psychotherapy? A systematic review of 3,4-methylenedioxymethamphetamine for Posttraumatic Stress Disorder treatment (Jóvenes en la Ciencia, 2026)
In recent decades, the prevalence of mental health diagnoses has increased significantly, with post-traumatic stress disorder (PTSD) standing out as one of the most common disorders due to adverse situations and greater functional impact. Although conventional interventions, such as trauma-focused cognitive behavioral therapy (TF-CBT) and selective serotonin reuptake inhibitors (SSRIs) for psychopharmacological treatment, are the first-line treatments, a considerable number of patients are resistant to these less effective treatments. In this context, MDMA (3,4-methylenedioxymethamphetamine)-assisted therapy has reemerged as a potentially effective alternative to facilitate emotional reprocessing and reduce traumatic avoidance, thereby facilitating therapeutic interventions. The objective of this study was evaluate the efficacy and safety of MDMA-assisted psychotherapy in the treatment of PTSD compared to conventional interventions or placebo. A systematic review was conducted following the PRISMA 2020 guidelines. The search was performed in PubMed, Scielo, and MEDLINE to identify articles published between January 2015 and August 2025. Randomized controlled clinical trials in adults diagnosed with PTSD were included. Three authors independently performed the selection, extraction, and assessment of risk of bias. The primary outcomes were reduction in PTSD symptoms based on the mean percentage reduction in CAPS/PCL-5 scores. The initial search identified [64] studies, of which [8] met the inclusion criteria. The results were synthesized narratively due to the heterogeneity of the studies. An average reduction of more than 50% in PTSD symptoms was observed in the groups treated with MDMA compared to the comparators. The FDA (Food and Drug Administration) designated MDMA as a “breakthrough therapy” for PTSD in 2017 and granted expanded access (“compassionate use”) in 2022, supporting its clinical potential. It suggests a promising, effective, and safe alternative; however, additional trials are required to confirm its long-term effects in addition to protocols and training for mental health professionals in the therapeutic use of substances.